2020
DOI: 10.1017/dmp.2020.324
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of 5 Early Warning Scores for Critical COVID-19 Patients

Abstract: Objective A simple evaluation tool for patients with novel coronavirus disease (COVID-19) could assist the physicians to triage COVID-19 patients effectively and rapidly. This study aimed to evaluate the predictive value of five early warning scores based on the admission data of critical COVID-19 patients. Methods Overall, medical records of 319 COVID-19 patients were included in the study. Demographic and clinical characteristics on admission were used for calculating the Standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 28 publications
(37 reference statements)
2
49
1
9
Order By: Relevance
“…As stated in the original, we agree quite well that SEWS, HEWS, NEWS and NEWS2 have the potential to be used as tools for screening severely and critically ill COVID-19 patients [1]. Meanwhile, another conclusion can be drawn that REMS does well in predicting the mortality risk of COVID-19 patients and it's the most accurate in this research, so we hold the view that REMS also has great potential in COVID-19 evaluation.…”
Section: Dear Editorsupporting
confidence: 72%
See 1 more Smart Citation
“…As stated in the original, we agree quite well that SEWS, HEWS, NEWS and NEWS2 have the potential to be used as tools for screening severely and critically ill COVID-19 patients [1]. Meanwhile, another conclusion can be drawn that REMS does well in predicting the mortality risk of COVID-19 patients and it's the most accurate in this research, so we hold the view that REMS also has great potential in COVID-19 evaluation.…”
Section: Dear Editorsupporting
confidence: 72%
“…The article by Hai Hu et al is very meaningful [1]. We agree that a series of Early Warning Scores, including Standardized Early Warning Score (SEWS), National Early Warning Score (NEWS), National Early Warning Score 2 (NEWS2) and Hamilton Early Warning Score (HEWS), have the potential to be used as screening tools for predicting the mortality risk of severe coronavirus disease (COVID-19) patients.…”
Section: Dear Editormentioning
confidence: 90%
“…Recent studies have shown that frailty and complaints general weakness, exhaustion, and low physical activity in elderly patients are related to the onset and prognosis of critical illness (23)(24)(25). NEWS has been reported to predict prognosis well in COVID 19 patients (26). Patients with OC43 had two-fold odds of requiring O 2 or intubation than those with other strains, while no difference in mortality or ICU admission was observed in a study of coronavirus-infected patients receiving acute care (8).…”
Section: Discussionmentioning
confidence: 99%
“…Myrstad et al [ 36 ] evaluated the ability of NEWS2 to predict seven-day mortality and Jang et al [ 23 , 37 ] evaluated the ability of NEWSs and qSOFA to predict 28-day mortality. Covino et al [ 23 ] and Gidari et al [ 14 ] studied whether NEWSs and other scores could predict the need for ICUs or Sixt et al [ 38 ] and Hu et al [ 39 , 40 ] analyzed the usefulness of NEWS2 at day 7 in relation to hospitalization. All of the aforementioned studies were developed using small cohorts (from 66 to 334 cases), different outcomes and with a limited number of EWSs studied.…”
Section: Discussionmentioning
confidence: 99%